Death in the Spinning House: Cambridge Prostitution and University Regulations by the Middle of the Nineteenth Century - Romero-Ruiz, María Isabel (My University, 2016)
The aim of this paper is to analyse the situation of prostitution in Cambridge and its regulation by the middle of the nineteenth century based on archival research. Cambridge Universitiy was characterised at the time by being a singular institution regarding its relationship with town and with the application of its own norms within its jurisdiction. As a consequence, the University of Cambridge had its own system of regulation of prostitution through a proctorial system within its boundaries and with a place of detention for prostitutes known as the Spnning House. In this place, located in Hobson’s Charity, St. Andrew’s Sreet, fallen women were confined for a number of days as a way of punishment for their immoral activity. In this University prison, women were detained under unsalubrious conditions which, on some occasions, ended in the premature death of some of the inmates. In particular, I am going to focus this paper on one case study: the death of Elizabeth Howe being a prisoner in the Spinning House in 1846. From the testimonies upon oath of a numer of witnesses, including the keeper, the surgeon, and family, and neighbours and friends of the deceased together with the depositions of the coroner and the verdict of the jury after the enquiry, a number of issues concerning the treatment of Cambridge prostitutes by University authorities can be discerned. Also the dreadful consequences of the system and the implication of different social agents can be discussed through the close reading and analysis of these primary sources.
Keywords: Prostitución - Reino Unido - S.XIX